Regulatory framework on import of hazardous and toxic materials : draft final report (Dhaka : Ministry of Environment and Forest, 1996)
Environment Management
1999-01-30
Keywords: Hazardous materials; Toxicology; Import; Legislation; Reports; Bangladesh